Part-Time Job and Students’ Academic Achievement - Safrul Muluk (SCAD Independent, 2017)
Part-time jobs have been considered as one of the factors influencing student’ academic achievement. This paper examines the students of English Department, at the Faculty of Teaching and Teacher Training, Ar-Raniry State Islamic University (UIN), Banda Aceh, Indonesia, undertaking part-time job outside campus. Effects of employment on students’ academic achievement are investigated. A qualitative approach is utilized to analyze the impact of part-time job on students’ academic achievement. Thirty (30) students were purposively chosen as the samples of this study. Students’ academic result in the form GPA, the amount of time spent on part-time job, as well as types of jobs the students involve in are scrutinized to see the relation between part-time jobs and their academic result. The result of the study indicates that despite the time spent on part-time job, students’ GPA are above average. However, in some cases, the time required to finish their studies is longer than those who do not have part-time jobs.